Comparison of the Effectiveness of Natural Coagulant Performance on% BOD Removal and% COD Removal in Pharmaceutical Industry Waste - Maharani, Agustin; Setiawan, Dwi; Ningsih, Erlinda (Tibuana, 2021)
Waste treatment can be done in variousways. One of the methods that can be used isthe coagulation and flocculation method. Thecoagulant used can be either a chemicalcoagulant or a natural coagulant. Naturalcoagulants can be used in wastewatertreatment for % removal of BOD and %removal of COD. By using moringa seedcoagulant, it showed % removal of BOD of90.12% and % removal of COD in thepharmaceutical industry waste a maximum of71.23%. Through the use of tapioca starchcoagulants, % removal of BOD and CODwas 95.25% and 94.63%. The use of smallcrab chitosan coagulant showed % removalof both BOD and COD’s results was 32%and 31%.